2014
DOI: 10.1007/s00253-014-6110-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of manufacturing processes on cell surface properties of probiotic strain Lactobacillus rhamnosus Lcr35®

Abstract: The influence of the industrial process on the properties of probiotics, administered as complex manufactured products, has been poorly investigated. In the present study, we comparatively assessed the cell wall characteristics of the probiotic strain Lactobacillus rhamnosus Lcr35® together with three of its commercial formulations with intestinal applications. Putative secreted and transmembrane-protein-encoding genes were initially searched in silico in the genome of L. rhamnosus Lcr35®. A total of 369 candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…boza). Moreover, Nivoliez et al (2015) obtained auto-aggregation values ranging from 16% to 31% and 12% to 21% for the probiotic strain L. rhamnosus Lcr35 after 3 and 5 h, respectively. Therefore, it is difficult to articulate a standard value for a high auto-aggregation value for Lactobacillus strains.…”
Section: Cell Surface Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…boza). Moreover, Nivoliez et al (2015) obtained auto-aggregation values ranging from 16% to 31% and 12% to 21% for the probiotic strain L. rhamnosus Lcr35 after 3 and 5 h, respectively. Therefore, it is difficult to articulate a standard value for a high auto-aggregation value for Lactobacillus strains.…”
Section: Cell Surface Propertiesmentioning
confidence: 94%
“…This includes the resistance to bile and low pH, gastric juices, and the ability to adhere and colonize gut epithelial (Bao et al, 2010;Del Piano et al, 2006). Furthermore, this also includes autoaggregation, co-aggregation, as well as microbial adhesion to solvents (MATS) (Nivoliez et al, 2015). Probiotics should also be resistant to antibiotics (Pinto, Franz, Schillinger, & Holzapfel, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial properties of microorganisms are usually evaluated with native culture strains. However, LBM are often administered as complex manufactured formulated products and positive impacts of the manufacturing process have been previously demonstrated in several studies [22][23][24] . In this study, we demonstrated that the vaginal formulation of Lactobacillus rhamnosus Lcr35, GYNOPHILUS, was able to kill C. albicans ATCC 10231 after 48 h, whereas the native strain alone only reduced the pathogen viability by 3 log 10 (CFU/ml) over the same length of time 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The LBP Gynophilus ® is vaginally delivered and is indicated to prevent recurrent VVC and BV by restoring vaginal health [ 11 – 13 ]. This LBP contains L. rhamnosus Lcr35 ® , which was previously reported to have potent antimicrobial properties [ 18 , 19 , 29 32 ]. Gynophilus ® (Lcr regenerans ® ) LBP formulated in vaginal capsules was shown to be well-tolerated and significantly enhanced the quality of life of women after treatment [ 13 ].…”
Section: Discussionmentioning
confidence: 99%